The Effect of the Problem Based Learning on EFL Learners’ Achievement - كاظم، شهد حاتم (جامعة بغداد - مركز البحوث التربوية والنفسية, 2014)
تناقش هذه الدراسة أسلوبا لتعلم بواسطة حل المشكلة كطريقة تدريس اللغة الإنكليزية في العراق. يهدف هذا الأسلوب إلى إشراك جميع المتعلمين في الأنشطة التعاونية وذلك هو الأسلوب الذي يركز على المتعلم. لتحقيق أهداف والتحقق من الفرضية التي تنص على " بأن ليس هناك فرق ذات دلالة إحصائية بين إنجازات المجموعة التجريبية والمجموعة الضابطة". تم اختيار ثلاثون متعلم لتكون عينة الدراسة. تم استخدام معادلة مان وتني لتحليل النتائج. بينت النتائج أنا عضاء المجموعة التجريبية الذين يتعلمون وفق الأساس التعلم بحل المشكلة حصلوا على درجات اعلى من أعضاء المجموعة الضابطة الذين تم تدريسهم وفق الطريقة التقليدية. التعلم بواسطة حل المشكلة له دور إيجابي على رفع مستوى تحصيل المتعلمين. في ضوء النتائج، وضعت عددا من الاستنتاجات والتوصيات والاقتراحات. The present study discusses the problem based learning in Iraqi classroom. This method aims to involve all learners in collaborative activities and it is learner-centered method. To fulfill the aims and verify the hypothesis which reads as follow” It is hypothesized that there is no statistically significant differences between the achievements of Experimental group and control group”. Thirty learners are selected to be the sample of present study.Mann-Whitney Test for two independent samples is used to analysis the results. The analysis shows that experimental group‟s members who are taught according to problem based learning gets higher scores than the control group‟s members who are taught according to traditional method. This means that problem based learning has positive effect on the learners‟ achievement. In the light of the results, a number of conclusions, recommendations and suggestions are put forward.
Keywords: تدريس اللغة الانجليزية; معلموا اللغة الانجليزية